Stink and the Ultimate Thumb-Wrestling Smackdown [Smraďo anglicky] / Book 6. - McDonald, Megan (Walker Books Ltd, 2020)
Meet Judy Moody's brother! Crackdown! Smackdown! Thwackdown!Stink Moody, family brain, brings home a report card that isn’t perfect? Yikes! Time for him to get into fighting shape and beat back that U for Unsatisfactory in PE! A scan of the sports channel leads to a knock-out find: world-class thumb wrestling, with tricky moves like Snake in the Grass and Santa’s Little Helper (no equipment needed, save for a tiny terrifying mask to sit on your thumb). But when Mom and Dad are not wowed, Stink gets another idea: he’ll kick and punch his way to a yellow belt with the help of a Dragon Master and a mind as still as a pond. Can you say Crouching Tiger, Hidden Thumb?